2002
DOI: 10.1124/jpet.300.3.925
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tachykinin NK1 Receptor Antagonists on the Viscerosensory Response Caused by Colorectal Distention in Rabbits

Abstract: Irritable bowel syndrome (IBS) is a common disorder mainly characterized by altered bowel habits and visceral pain. In this study, we investigated the role of tachykinin NK 1 receptors in the visceral pain response (abdominal muscle contraction) caused by colorectal distention in rabbits previously subjected to colonic irritation, using the selective tachykinin NK 1 receptor antagonists TAK-637 [(aR,9R)-7-[3,5-Bis(trifluoromethyl)benzyl]-8,9,10,11-tetrahydro-9-methyl-5-Intracolorectal administration of 0.8% ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 40 publications
0
39
0
Order By: Relevance
“…For this purpose, we used a rabbit CRD model based on the pharmacologically validated model reported by Okano et al (10). Using this disease model, a series of compounds were evaluated and were found to inhibit the VMR to CRD in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, we used a rabbit CRD model based on the pharmacologically validated model reported by Okano et al (10). Using this disease model, a series of compounds were evaluated and were found to inhibit the VMR to CRD in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery was performed according to the previously reported procedure (10). Under ketamine/xylazine anesthesia, the lower left abdominal musculature was exposed.…”
Section: Colorectal Distension (Crd) and Hypersensitivity In Rabbitsmentioning
confidence: 99%
“…As described previously (19), all surgical procedures were performed under pentobarbital sodium anesthesia. The lower left abdominal musculature (abdominal external oblique muscle) was exposed, and a force transducer was attached for monitoring abdominal muscle contractions, that is, the visceromotor response (VMR) to CRD.…”
Section: Colorectal Distension (Crd) and Hypersensitivity In Rabbitsmentioning
confidence: 99%
“…Our study clearly demonstrated that TAK-480 possesses a unique property showing species-related differences in the binding affinity for the NK 2 receptor (higher affinity for human, rabbit, and guinea pig in nM order and lower affinity for rat in μM order) in accordance with heterogeneity of the receptor (18). Therefore, we investigated the efficacy of TAK-480 in non-rodent animal models partially-modified from original ones: a rabbit model of zymosan-induced visceral hypersensitivity and a guinea-pig model of ricinoleic acid-induced defecation, which partially mimic common characteristics of IBS (19,20). In addition, we examined NK 2 -receptor antagonism in isolated human colon specimens to further predict the clinical efficacy of TAK-480.…”
Section: Introductionmentioning
confidence: 99%
“…A flexible latex balloon catheter was surgically placed into the stomach though a small incision at the forestomach. A force transducer (F-08IS; StarMedical, Tokyo) was then sutured to the abdominal external oblique muscle as previously reported (14,16) to measure the number of abdominal contractions as an indicator of visceral pain sensation.…”
Section: Surgical Proceduresmentioning
confidence: 99%